Peran Kepemimpinan dalam Sinergi antar Dinas di Pemerintahan Daerah: Studi Program Percepatan Peningkatan Status Kemajuan dan Kemandirian Desa di Provinsi Kalimantan Barat - Siti Fatmawati (Jurnal Kawistara, 2021)
The role of leadership has been seen critical in the success of achieving the goals of the organization. Leadership is manifested through the leaders’ competence and capabily. In this perspective, many see the value of transformational leadership in implementing the program for promoting independent village program. The role of transformational leaders has become a key factor in bringing regional progress. The West Kalimantan Province is an example of the critical role a transformational leader as manifested at least by a Governor of West Kalimantan in his role between different government agencies (SKPD) in the independent village program. Based on the case study of West Kalimantan, This research aims to examine the role of the leadership role of the Governor of West Kalimantan in the independent village program. The research used a qualitative approach with case studies. Data are collected through structured interviews and document review and field observations. Some of the informants involved were officials in the West Kalimantan Provincial Government. The results showed that the leadership role of the Governor of West Kalimantan has succeeded in increasing the status of an independent village. The success of the independent village program has become a top priority as stated in the Governor’s Decree. The Governor’s involvement in building synergies between SKPDs has shown a spirit of transformational leadership that can be demonstrated as an innovator, motivator, facilitator and mobilizer.